COMPLEX REGIONAL PAIN SYNDROME (CRPS) : SEBUAH TINJAUAN PUSTAKA - Diki Wahyudi (Yayasan Pendidikan Medika Indonesia, 2023)
Complex Regional Pain Syndrome (CRPS) is a chronic pain condition (lasting more than six months) that most often affects one limb (arm, hand or leg) after an injury. CRPS is believed to be caused by damage to, or malfunction of, the peripheral and central nervous systems. The most common injury causing CRPS is a fracture. A large multicenter prospective study found that 48.5% of patients developed CRPS (IASP criteria) after sustaining ankle, wrist, and metatarsal fractures. Management in CRPS patients is a combination of physical/occupational therapy, psychological therapy, neuropathic pain medication, and anti-inflammatory drugs. The management aims to reduce pain, increase mobility, and improve the quality of life of CPRS patients.